A Population-Based Survey of the Workplace Costs for Caregivers of Persons With Treatment-Resistant Depression Compared With Other Health Conditions. Issue 9 (September 2020) - Lerner, Debra; Lavelle, Tara A.; Adler, David; Chow, Wing; Chang, Hong; Godar, Sean C.; Rogers, William H.
Abstract : Objective: To describe caregiving work outcomes and related indirect (ie, productivity) and direct (ie, caregiving hours and expenses) costs. Methods: A national, population-based survey to identify employed caregivers assisting a person with treatment-resistant depression (TRD) and a comparison group of employed caregivers assisting others (No TRD). Results: Screening identified 169 TRD caregivers and 1070 No TRD caregivers providing 23.3 and 14.6 mean weekly caregiving hours, respectively. Adjusted annual indirect cost estimates were $11, 121 for caregivers of TRD and $7761 for caregivers in the No TRD group ( P  ⩽ 0.0001). At-work productivity loss (presenteeism) was the largest component. Adjusted annual direct cost estimates were $29, 805 for caregivers of TRD and $20, 642 for caregivers in the No TRD group ( P  ⩽ 0.0001). Conclusions: TRD exacts a toll on caregivers and their employers exceeding that for other caregivers. Abstract : Supplemental Digital Content is available in the text